Viscosity investigation on metastable hydrate suspension in oil-dominated systems. (20th July 2021) - Liu, Zaixing; Liu, Weiguo; Lang, Chen; Liu, Ran; Song, Yongchen; Li, Yanghui
Highlights: A new viscosity model for hydrate slurry was proposed. A non-dimensional parameter of the aggregation ratio of hydrate particles was introduced. Rheological measurement of methane hydrate slurry were conducted. The viscosity model developed is applicable to various hydrate slurries. Abstract: Predicting the viscosity of hydrate slurries is essential in evaluating the transport performance of oil and gas in deep-water pipelines and the risk of blockage. In this work, based on the Camargo–Palermo model and the bimodal suspension model, a new viscosity model was developed for hydrate slurries. In this model, the viscosity of slurry is determined jointly by small hydrate particles and larger hydrate aggregates, in which the maximum critical diameter of the aggregate is controlled by shear force and cohesion force, while amount of hydrate particles and aggregates can be described by a dimensionless parameter proposed. In addition, rheological measurements of methane hydrate slurry formed from water-in-oil emulsion were conducted with a high-pressure rheometer to validate the developed model. The predictions of the model agree well with the experimental data for metastable hydrate suspension in oil-dominated systems with either different initial water cuts or different water conversion rates.